Safety and efficacy of a feed additive consisting of zearalenone hydrolase produced by Escherichia coli DSM 32731 for all terrestrial animal species (Biomin GmbH). (24th February 2022) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Fašmon Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on zearalenone hydrolase (ZenA) produced by Escherichia coli DSM 32731 when used as a feed additive for all terrestrial animals. The production strain E. coli DSM 32731 is genetically modified and harbours a kanamycin resistance gene. No viable cells of the production strain were detected in the final product, but uncertainty remains on the presence of recombinant DNA in the final product. The ZenA contained in the additive is safe for all terrestrial animal species up to the maximum use levels of (in U/kg complete feed): 100 U/kg in chickens for fattening; 150 U/kg in laying hens, turkeys for fattening and rabbits; 200 U/kg in pigs; 250 U/kg in dairy cows; 400 U/kg in veal calf (milk replacer), cattle for fattening, sheep, goats, horses and cats; and 450 U/kg in dogs. Based on the ADME and toxicological data, the FEEDAP Panel considers that the use of the ZenA contained in the additive in animal nutrition is safe for the consumers. The endotoxin content in the additive poses a risk by inhalation for users handling the additive. The additive is not a skin/eye irritant nor a skin sensitiser. Due to its proteinaceous nature, the additive should be considered as a potential respiratory sensitiser. The ZenA contained in the additive and the resulting breakdown products of its enzymatic activity do not represent a safety concern for the environment. The production strain harbours an antimicrobial resistance gene and uncertainties remain on the possible presence of its recombinant DNA in the final product; therefore, the FEEDAP Panel cannot conclude on safety of the additive for the target species, the consumer, the user and the environment.